2018
DOI: 10.1002/cctc.201801381
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novel Aromatic‐Aliphatic Poly(ketone ester)s through Condensation of Biomass‐Derived Monomers

Abstract: Novel unsaturated and saturated monomers with a hydroxyl group and a carboxylic group via aldol condensation reaction of lignin‐derived aromatic aldehydes with levulinic acid were prepared through organocatalysis and hydrogenation, respectively. The catalytic process was optimized and the structure of the monomers were full characterized. The as‐prepared monomers were ready for the subsequent condensation polymerization to achieve a serial of novel full biobased poly(ester ketone)s. The chemical‐physical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…It is also find that oxidative post‐polymerization modification can significantly change the thermal behavior of the poly(thioether carbonate)s, as evidenced by the DSC curve of PO2a3a (Figure 3b). There is a clear crystallization peak (111 °C) and a melting peak (166 °C), consisting with its WXRD patterns (Figure S39), and the T g is significantly increased from −7 °C to 61 °C after the oxidation, which is comparable to those of PLA and PET [33] . This can be explained by that the tetrahedral structure of the sulfone group may restrict the rotation of the C−S bond, thereby reducing the mobility of the macromolecular chain, thus leading to an increase in T g [23,28, 32] .…”
Section: Resultsmentioning
confidence: 83%
“…It is also find that oxidative post‐polymerization modification can significantly change the thermal behavior of the poly(thioether carbonate)s, as evidenced by the DSC curve of PO2a3a (Figure 3b). There is a clear crystallization peak (111 °C) and a melting peak (166 °C), consisting with its WXRD patterns (Figure S39), and the T g is significantly increased from −7 °C to 61 °C after the oxidation, which is comparable to those of PLA and PET [33] . This can be explained by that the tetrahedral structure of the sulfone group may restrict the rotation of the C−S bond, thereby reducing the mobility of the macromolecular chain, thus leading to an increase in T g [23,28, 32] .…”
Section: Resultsmentioning
confidence: 83%
“…While using TC or FC, polyesters with high Tg were obtained ( Table 1, PE3 and 4), the Tg of PE-4 is similar to PE-3 indicating that the furan-based polyester has similar properties to the benzene-based polyester, and their Tgs are much higher than that of PBT (38 °C ). Compared with PE-3, PE-5 showed increased Tg as the rigidity of the diol increased and both their Tgs are comparable or even higher than those of PBT and PET (38 and 67 °C , respectively) [31]. Although no melting point was observed for any of these polyesters, the XRD results indicated that the PE-2 is amorphous, whilst the other polyesters contain partial crystalline regions ( Figure 5).…”
Section: Molecular Thermal and Xrd Analysis Of Pesmentioning
confidence: 95%
“…The shortcoming of this study lies with the use of high cost and relatively environmentally unfriendly chloroalkyl alcohols. Chen et al obtained a series of new bio-based polyesters by the polycondensation of novel monomers with hydroxyl and carboxyl groups prepared by aldol condensation of aromatic aldehydes with levulinic acid [31]. Although significant achievements have obtained during the past five years, some of studies still suffered drawbacks of using complex, multiple synthetic steps and non-sustainable feedstocks to prepare polymeric monomers.…”
Section: Introductionmentioning
confidence: 99%
“…202,203,[211][212][213] For example, the polymer obtained with dimethyl succinate (Scheme 4 ( 7)) exhibited a T g similar to PET (68 °C) and a storage modulus of 5.1 GPa. 202 Scheme 4 Representative multitude of vanillin-(1, 197 2, 198 3 & 4, 199 5, 200 6, 201 7, 202 8 203 ), vanillic acid-(9, 204-206 10, 204,207 11, 208 12, 205,209 13, 209 14, 210 15, 211,212 16, 213 17, 208 18 214 ), and ferulic acid-(19, 215 20, 216 21, 217 22, 218 Mankar et al designed a spiro-diol vanillin-based monomer, whose synthesis remarkably produced lower GHG emissions than biobased 1,3-propanediol and afforded a transparent material after polymerization (Scheme 4 ( 8)). 203 Finally, it is noteworthy that polymer 16 from Scheme 4 exhibited better mechanical properties than PET.…”
Section: Lignin-based Thermoplastic Polymersmentioning
confidence: 99%
“…Scheme 4 Representative multitude of vanillin-(1,197 2, 198 3 & 4,199 5,200 6,201 7,202 8 203 ), vanillic acid-(9, 204-206 10, 204,207 11,208 12, 205,209 13,209 14,210 15, 211,212 16,213 17,208 18214 ), and ferulic acid-(19,215 20,216 21,217 22,218 23 209 ) based thermoplastic polyesters.…”
mentioning
confidence: 99%